Changes in physical properties of sweet potato due to effects of thermal pre-treatments for puree production - Sonia Gallego-Castillo; Alfredo Adolfo Ayala-Aponte (Dyna, 2018)
In response to increasing consumer demand for high-quality, easy-to-prepare foods, it is necessary to develop innovative ways to use roots and tubers, such as sweet potatoes, in processed foods. Thus, two thermal processes were evaluated, freezing-cooking (F+C) and blanching-freezing-cooking (B+F+C) on the physical properties of the orange-fleshed sweet potato (OFSP) cultivar, which has a high content of β-carotene, in terms of drip loss (Δm), volume variation (ΔV), color, and texture. Cylindrical samples of OFSP were used. Blanched and unblanched samples were stored by freezing, at -18 °C for 2 months, and subsequently cooked at 95 °C. The blanching process was carried out at 95 °C for 2 min. The results showed that, when blanching was used as a pre-treatment for freezing-cooking, a product with fewer physical changes, with a lighter and more intense color (chroma), and with a lower loss of elasticity (Ed) and firmness (F) was obtained.